Arte povera - Christov-Bakargiev, Carolyn (London : Phaidon, 1999)
Anselmo, Giovanni ; Boetti, Alighiero ; Calzolari, Pierpaolo ; Ceroli, Mario ; Cintoli, Claudio ; Fabro, Luciano ; Gilardi, Piero ; Icaro, Paolo ; Kounellis, Jannis ; Long, Richard ; Mattiacci, Eliseo ; Mauri, Fabio ; Merz, Mario ; Merz, Marisa ; Mondino, Aldo ; Paolini, Giulio ; Pascali, Pino ; Patella, Luca Maria ; Penone, Giuseppe ; Piacentino, Gianni ; Pistoletto, Michelangelo ; Prini, Emilio ; Zorio, Gilberto
boek